Primary Circulating Prostate Cells Are Not Detected in Men with Low Grade Small Volume Prostate Cancer - Murray, Nigel P. (Hindawi Publishing Corporation, 2014)
Objective. To determine if primary circulating prostate cells (CPCs) are found in all men with prostate cancer. Methods and Patients. A prospective study, to analyze all men with an elevated PSA between 4.0 and 10.0 ng/mL undergoing initial biopsy. Primary CPCs were obtained by differential gel centrifugation and detected using standard immunocytochemistry using anti-PSA; positive samples underwent a second process with anti-P504S. A malignant primary CPC was defined as PSA (+) P504S (+) and a test positive if 1 cell/4 mL was detected. Biopsy results were registered as cancer/no-cancer, number of cores positive, and percent infiltration of the cores. Results. 328/1123 (29.2%) of the study population had prostate cancer diagnosed on initial biopsy, and 42/328 (12.8%) were negative for primary CPCs. CPC negative men were significantly older, and had lower PSA levels, lower Gleason scores, and fewer positive cores and with infiltration by the cancer. 38/42 (91%) of CPC negative men complied with the criteria for active surveillance in comparison with 34/286 (12%) of CPC positive men. Conclusions. Using primary CPC detection as a sequential test to select men with an elevated PSA for biopsy, the risk of missing clinically significant prostate cancer is minimal when the patient is primary CPC negative; less than 0.5% of all primary CPC negative men had a clinically significant prostate cancer.